Expansion of vector triple product || Proof of A×(B×C)=B(A.B)-C(A.B)

preview_player
Показать описание
Expansion of vector triple product
A×(B×C) = B(A.B) - C(A.B)
A×(B×C)=B(A.B)-C(A.B)
vector triple product proof
vector triple product bsc
#physicsbyashishkapoor
#vectortripleproduct
#bsc

Proof of A.(B×C)=B.(C×A)=C.(A×B)

Scalar field and vector field, gradient of vector field
Рекомендации по теме
Комментарии
Автор

Thanks sir ji🙏aaj maine ise sikh liya 😊

AnjaliKumari-iskf
Автор

The proof is great, thank you for making the video, wondering is there any shorter method to prove the same.

storiesforever